The Effect of Quality of Education Services on Perceptions of Educational Costs and Student Trust and Their Impact on Student Satisfaction at SMA Negeri Ujungbatu - Septia Syafriani; Suarman Suarman; Henny Indrawati (Universitas Riau, 2021)
This study aims to analyze the effect of the quality of education services on perceptions of education costs and student confidence and their impact on student satisfaction at SMA Negeri Ujungbatu. The population of this research is the students of Class XI SMA Negeri Ujungbatu as many as 475 students. The study was conducted with a sample of 217 students taken by simple random sampling technique. Data was collected using a questionnaire. The data analysis used in this research is descriptive quantitative and path analysis. The results showed that there was an influence between the quality of education services on perceptions of education costs and student confidence and the impact on student satisfaction at SMA Negeri Ujungbatu. The meaning is that the better the quality of educational services provided by the school and the more positive students perceive the cost of education, the more students will believe in the education in the school, it will increase the satisfaction felt by students